Предмет: Алгебра, автор: Wuwuwuwuwuwuwu

Упростите выражение
(3a/a+6 - 2a/a²+12a+36) : 3a+16/a²-36 +
6(a-6)/a+6

Ответы

Автор ответа: sulismanaliev95
1

( \frac{3a}{a + 6}  -  \frac{2a}{ {(a + 6)}^{2} } ) \div  \frac{3a + 16}{(a + 6)(a - 6)}  +  \frac{6(a - 6)}{a + 6}   =  ( \frac{3a(a + 6) - 2a}{ {(a + 6)}^{2} }    -

 \frac{3 {a}^{2}  + 18a - 2a}{ {(a + 6)}^{2} })  \times  \frac{(a + 6)(a - 6)}{3a + 16}  +  \frac{6(a - 6)}{a + 6}  =   \frac{a( a- 6) + 6a - 36}{a + 6}   =  \frac{ {a}^{2}  - 36}{a + 6}   =  a - 6

Похожие вопросы